Diameter Criteria Have Limited Value for Prediction of Functional Dialysis Use of Arteriovenous Fistulas. (October 2018) - Wilmink, Teun; Corte-Real Houlihan, Maria
Abstract : Objective: To determine the value of diameter measurements for prediction of functional dialysis use (FDU) of arteriovenous fistulas (AVF). Methods: Review of access operations and dialysis databases from January 1, 2007 to August 1, 2015. Follow up until July 1, 2016. FDU defined as six consecutive dialysis sessions with two needles on the AVF. Artery and vein diameters measured by portable ultrasound in access clinic. Contribution of diameter to predict FDU assessed with logistic regression. Diagnostic accuracy assessed by sensitivity, specificity, positive and negative predictive values (PPV and NPV). Results: 803 AVF operations were analysed: 507 (63%) radiocephalic fistulas (RCAVF), 237 (30%) brachiocephalic fistulas (BCAVF), and 59 (7%) brachiobasilic fistulas (BBAVF). Women had lower FDU in RCAVF (0.65, 95% CI 0.58–0.72 vs. 0.86, 95% CI 0.81–0.89; p  < .0001), but not in BCAVF (0.83, 95% CI 0.75–0.89 vs. 0.81, 95% CI 0.73–0.88; p  = .75). Female gender was an independent negative predictor of FDU in RCAVF (OR 0.31; 95% CI 0.20–0.49). Vascular kidney disease was an independent negative predictor for FDU in RCAVF (OR 0.33; 95% CI 0.17–0.64) and BCAVF (OR 0.22; 95% CI 0.09–0.57) in multivariable analysis. Artery and vein diameter did not improve the model for RCAVF. Vein diameter as categorical variable improved the model for BCAVF. Diameter cut off of radial artery ≥ 2 mm has 96% sensitivity, 86% PPV, 9% specificity, and 29% NPV in men. Radial artery diameter ≥2 mm had 96% sensitivity, 67% PPV but 13% specificity and 62% NPV in women. Conclusions: Diameter is a poor predictor of FDU of AVF. Arterial diameter measurements add no diagnostic value for BCAVF. Poor specificity suggests a diameter under 2 mm at the wrist should not preclude AVF formation. Vascular kidney disease is an independent negative predictor for FDU in all AVF.